1995
DOI: 10.1111/1523-1747.ep12320329
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist Suppresses Contact Hypersensitivity

Abstract: Interleukin-1 receptor antagonist (IL-1ra), a naturally occurring inhibitor of interleukin-1 (IL-1), blocks IL-1 binding to its receptors but has no agonistic activity. IL-1 is thought to play an important role in contact hypersensitivity (CHS), although the effects of exogenously administered IL-1 in CHS have been somewhat controversial. To clarify the role of IL-1 in CHS, we studied the effect of IL-1 receptor blockade using exogenous IL-1ra and evaluated these effects on CHS. We examined the in vivo effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 41 publications
2
49
0
6
Order By: Relevance
“…1) and exhibits properties consistent with those of an allosteric negative modulator. As a competitive inhibitor of IL-1, IL-1ra interferes with all actions of IL-1RI, including desirable ones related to innate immunity, and hence increases the risk of cancer and seemingly of infections (85). In this report, we have described the first small molecule (peptide) antagonist of a cytokine receptor, notably of IL-1RI, which seems to integrate allosteric modulatory properties; 101.10 is specific, potent and effective in vitro and in vivo in (IL-1-implicated) models of inflammation after systemic and topical applications.…”
Section: Discussionmentioning
confidence: 99%
“…1) and exhibits properties consistent with those of an allosteric negative modulator. As a competitive inhibitor of IL-1, IL-1ra interferes with all actions of IL-1RI, including desirable ones related to innate immunity, and hence increases the risk of cancer and seemingly of infections (85). In this report, we have described the first small molecule (peptide) antagonist of a cytokine receptor, notably of IL-1RI, which seems to integrate allosteric modulatory properties; 101.10 is specific, potent and effective in vitro and in vivo in (IL-1-implicated) models of inflammation after systemic and topical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination has also revealed the infiltration of basophils and eosinophils in the superficial dermis as the characteristics of the animal skin reaction (Sugawara et al, 1993). Studies have demonstrated that the local release of cytokines, including TNF-α, IL-1, and IFN-γ, is critical for the optimal generation of the CHS and that TNF-α is believed to play a role in the pathogenesis of asthma in humans and asthma and CHS in animal models (Piguet et al, 1991;Kondo et al, 1995;Wang et al, 2003). TNF-α, which is recognized as a powerful mediator of inflammatory reaction, might induce these alterations either directly, since it can react with a wide range of cell types (Beutler and Cerami, 1989), or indirectly by the activation of several other cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that local release of cytokines, including TNF-α, IL-1, and IFN-γ, is critical for the generation of the CHS reaction (Piguet et al, 1991;Kondo et al, 1995;Wang et al, 2003). TNF-α is a pleiotropic cytokine involved in host defense mechanisms and inflammatory responses (Vassalli, 1992;Shah et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of CHS found that pro-inflammatory effects such as the induction of TNF-a, IFN-g, IL-1 secretion [10,16,23,24] and expression of ICAM-1, VCAM-1, ELAM-1 [7,28] constitute an important process for the elicitation phase of CHS. Since these pro-inflammatory effects of haptens are non-immunological in nature, they do not require Ag-specific recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of Langerhans cells (LCs), antigen (Ag) recognition of T and B cells, cytokine synthesis, and cell adhesion molecules have also been analyzed [1,4,5,7,10,15,16,23,24,27,28]. T cell clones derived from peripheral blood and dermal tissues of CHS patients and mice were studied, and most of these phenotypes have been found to possess CD4 + [20].…”
Section: Introductionmentioning
confidence: 99%